A community based cross-sectional study on compliance and barriers of iron and folic acid consumption among postnatal mothers of 0-6 weeks in an urban area from central India - P., Thungamithirai; Dhoble, Manjusha A.; W. Narlawar, Uday; S. R., Shilpa; Bembade, Shubhangi S.; P., Ajaya Krishnan (International Journal Of Community Medicine And Public Health, 2024)
Background: Iron deficiency anemia is becoming prevalent in postpartum women who are not aware about the importance of iron and folic acid (IFA) consumption. There might be many barriers which ultimately result in noncompliance. Thus, this study aimed in assessing compliance and barriers of IFA consumption among postnatal women. Methods: A cross-sectional study was conducted in 175 postnatal mothers in an urban area from Nagpur. A semi-structured questionnaire was used to assess the compliance and barriers to IFA consumption. Adherence level was assessed using the Morisky medication adherence scale. Results: The study found that 71% of the study participants were compliant to IFA consumption. Among the non-adherent participants, the main barrier found was the knowledge barrier and the prevailing side effects. According to the Morisky medication adherence scale, the majority exhibited a strong adherence. Conclusions: About three fourth of the participants were compliant to IFA consumption. Compliance was found significant among those who were primigravida, higher monthly income, received health education regarding IFA and intake of IFA during ANC period. Considering the barriers observed in the study the major recommendation will be to improve the palatability and enhance the health education.